2002
DOI: 10.1039/b202680e
|View full text |Cite
|
Sign up to set email alerts
|

Are metastable, precrystallisation, density-fluctuations a universal phenomena?

Abstract: In-situ observations of crystallisation in minerals and organic polymers have been made by simultaneous, time-resolved small angle X-ray scattering (SAXS) and wide angle X-ray scattering (WAXS) techniques. In isotactic polypropylene slow quiescent crystallisation shows the onset of large scale ordering prior to crystal growth. Rapid crystallisations studied by melt extrusion indicate the development of well resolved oriented SAXS patterns associated with long range order before the development of crystalline p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 67 publications
2
42
0
Order By: Relevance
“…Experimental observations of a SAXS signal intensity increase, before the onset of a WAXS signal (i.e., crystal Bragg peaks), during the very early stages of crystallization were reported for PET, [28][29][30][31] iPP, 32,33 and PE. 34 This was claimed to be due to a precrystalline orientation in the melt and was sometimes explained on the basis of linearized Cahn-Hilliard theory of spinodal decomposition.…”
Section: Mesomorphic Meltmentioning
confidence: 99%
“…Experimental observations of a SAXS signal intensity increase, before the onset of a WAXS signal (i.e., crystal Bragg peaks), during the very early stages of crystallization were reported for PET, [28][29][30][31] iPP, 32,33 and PE. 34 This was claimed to be due to a precrystalline orientation in the melt and was sometimes explained on the basis of linearized Cahn-Hilliard theory of spinodal decomposition.…”
Section: Mesomorphic Meltmentioning
confidence: 99%
“…In polymer phase separation, experimental methods provide evidence of microphase separation caused by chemical polydispersity of the copolymers [20]. In crystallisation, results "suggest prenucleation density fluctuations, leading to a metastable phase, play an integral role in all three classes of crystallisation" [21]. The use of a distribution in critical flux could be a way to account for the existence of a metastable phase preceding the spinodal decomposition when considering the phase transition leading to the formation of a colloidal deposit on a membrane interface;…”
Section: Dfc and Phase Transitionmentioning
confidence: 99%
“…Both observed that increasing the haul-off speed of the fibre increased the orientation and lamellar repeat distances, thus the morphology changed from spherulitic to a sheaf-like structures. Further to this, earlier publications by the authors [29][30][31] have detailed SAXS/WAXS studies on extrusion of polypropylene tapes, which concentrated on observing the onset of large-scale ordering prior to any crystalline growth. The onset was revealed by the development of intensity in the SAXS data before crystalline peaks in the WAXS data are observed.…”
Section: Introductionmentioning
confidence: 99%